Pediatric Infectious Diseases Revisited - Wirth, Stefan; SpringerLink (Online service) (Basel : Birkhäuser Basel : Imprint: Birkhäuser, 2007)
The successful prevention of childhood diseases like diphtheria, tetanus and pertussis has made a major contribution to the improvement of public health, and vaccines and a variety of drugs are amongst the most fruitful applications of 20th-century research. Today pediatric infectious disease research is closely interconnected with other disciplines. Understanding the biology of the causative agents and the pathogenesis of disease is an essential step in achieving control and elimination of the diseases. Starting with historical, epidemiological and sociocultural issues, the volume presents clinical as well as molecular biological aspects of pediatric infectious diseases. New insights into the pathogenesis of infection are presented and an update on diagnostics, prevention and treatment of pediatric viral, fungal and bacterial diseases provided. The role of emerging new pathogens is also highlighted. The book aims at an interdisciplinary audience of clinicians and non-clinicians: pediatricians, infectious disease researchers, virologists, microbiologists, public health politicians and university libraries.
Global control of infectious diseases by vaccination programs -- Potential impact of rotavirus vaccination on the mortality of children in developing countries -- Controversially discussed indications for immunization -- Gonorrheal ophthalmia neonatorum: Historic impact of Credé’s eye prophylaxis -- Malnutrition and infection in industrialized countries -- Better education through improved health and nutrition: implications for early childhood development programs in developing countries -- Early childhood caries and childhood periodontal diseases -- Role of the blood-brain barrier and blood-CSF barrier in the pathogenesis of bacterial meningitis -- The molecular basis of paediatric malarial disease -- Epidemiology and etiology of Kawasaki disease -- Helicobacter pylori infection in children -- Human metapneumovirus infection -- Avian influenza viruses: a severe threat of a pandemic in children? -- Human papillomavirus infections in children -- New treatments for hepatitis B and C in children and adolescents -- Invasive fungal infections in children: advances and perspectives -- Pediatric aspects of bioterrorism -- Pediatric infectious diseases — Quo vadis 2015?.
Keywords: Medical microbiology; Immunology; Infectious diseases; Pediatrics; Medical Microbiology; Immunology; Infectious Diseases; Pediatrics